Management of Resectable Gastric Cancer - Cowdell, Imogen; Culver, Emma (Journal of the Nuffield Department of Surgical Sciences, 2023)
Gastric cancer is one of the commonest malignancies worldwide and is the fourth leading cause of cancer-related death. Commonly presenting at an advanced stage, the prognosis of gastric cancer is dismally poor, with an overall five-year survival of around 15%. Here, I present one typical case, Mr AB, who was diagnosed with stage T3N1M0 gastric adenocarcinoma and underwent total gastrectomy with D2 lymphadenectomy and perioperative chemotherapy. This report will go on to examine the evidence base surrounding the management of non-early resectable gastric cancer relevant to Mr AB’s case, in particular D1 versus D2 lymphadenectomy and neoadjuvant chemo-radiotherapy.